Penyuluhan Kesehatan tentang Deteksi Dini Kanker Serviks pada WUS - Siti Nurdiyana; Heny Puspasari; Yosi Yusrotul Khasanah; Agi Yulia Ria Dini (Health Care : Journal of Community Service, 2025)
Cervical cancer is the uncontrolled growth of cells (cancer) in the cervix. All women are at risk of developing this cancer. However, sexually active women are more likely to be affected. In its early stages, cervical cancer usually does not cause easily recognizable symptoms. The most common symptom is abnormal bleeding, for example, bleeding after sex, outside the menstrual cycle, or after menopause. The benefits and objectives of this outreach program are expected to improve women's knowledge and quality of life regarding cervical cancer prevention. The method used in this program is to provide health education through counseling about cervical cancer and cervical cancer prevention practices such as proper vaginal hygiene. Based on a self-awareness survey, the most common problem identified was a lack of knowledge about cervical cancer and a lack of awareness of early cervical cancer prevention methods. The priority problem was the lack of knowledge among the Sawangan Village community about early cervical cancer detection in women of childbearing age (WUS). To address this, we implemented one effort by conducting outreach on cervical cancer for women of childbearing age (WUS) and providing guidance on proper vaginal hygiene to prevent cervical cancer. After the outreach and practice of cervical cancer prevention, participants had a better understanding of cervical cancer and how to prevent it.